Efficacy of soap and water based skin decontamination using in vivo animal models: a systematic review. (3rd October 2021) - Burli, Anuk; Kashetsky, Nadia; Feschuk, Aileen; Law, Rebecca M.; Maibach, Howard I.
ABSTRACT: Water-only or soap and water solutions are considered a gold standard for skin decontamination. However, there is lack of conclusive data regarding their efficacy. The aim of this study was to summarize in vivo animal model data on skin decontamination using water-only, and/or soap and water. Covidence, Embase, MEDLINE, PubMed, Web of Science, and Google Scholar were searched to identify relevant articles using water-only or soap and water decontamination methods in in vivo animals. Data extraction was completed from studies, representing three animal models, and 11 contaminants. Results demonstrated water-only decontamination solutions led to complete decontamination in 3.1% (n = 16/524) protocols, incomplete decontamination in 90.6% (n = 475/524) of protocols, and mortality in 6.3% (n = 33/524) of protocols. Soap and water decontamination solutions resulted in complete decontamination in 6.9% (n = 8/116) protocols, incomplete decontamination in 92.2% (n = 107/116) of protocols, and mortality in 6.9% (n = 8/116) of protocols. Although water only, or soap and water is considered a gold standard for skin decontamination, most papers investigated found that water only, and soap and water provided incomplete decontamination. Due to the insufficient data, and limitations that hinder the applicability of available data, evidence indicates that more contemporary studies investigating skin decontamination are needed, and compared to other model species, including humans, when practical.